Preventiva duševnega zdravja v učnih načrtih na predmetni stopnji osnovne šole - Britovšek, Karmen (Pedagoška obzorja, 2015)
Mental health care of young people has become an important area of national mental health programs. Good mental health of young people is related to health of general population and contributes to societal welfare. The aim of our study was to examine the extent to which the syllabuses in Slovenian upper elementary schools (Grades 6-9) include learning goals in domains of mental health prevention. The research showed that there are only few operational learning goals, which are closely connected to the domain of mental health prevention. Most of these learning goals are included in the course Civic education and ethics and relate to physical and social field of mental health prevention. Emotional/psychological and intellectual domains of mental health prevention are present to a lesser extent. Based on these results, we may conclude that more school activities should be dedicated to mental health issues in existing syllabuses.
Keywords: curriculum; učni načrti; osnovne šole; elementary schools; mental health; duševno zdravje; prevention; preventiva